A Literature Synthesis Indicates Very Low Quality, but Consistent Evidence of Improvements in Function after Surgical Interventions for Primary Osteoarthritis of the Elbow. (30th January 2013) - Vincent, Joshua I.; Vandervoort, Anthony A.; MacDermid, Joy C.
Abstract : Background . Primary osteoarthritis of the elbow is a debilitating disease with an overall incidence of about 2%. Pain and reduced motion (ROM) lead to disability and loss of functional independence. Purpose . To critically review the literature on patient-related important functional outcomes (pain, ROMs and functional recovery) after surgery for primary OA of the elbow, utilizing the 2011 OCEBM levels of evidence. Design . A literature synthesis. Results . Twenty-six articles satisfied the inclusion and exclusion criteria; 25 of the studies were at level IV evidence, and 1 at level III. All three surgical techniques led to improvement in pain, ROM, and functional recovery in the short- and medium-term follow-up. Long-term follow-up results, available only for open joint debridement, showed recurrence of osteoarthritic signs on X-ray with minimal loss of motion. Recently, there seems to be an increased focus on arthroscopic debridement. Conclusion . The quality of research addressing surgical interventions is very low, including total elbow arthroplasty (TEA). However, the evidence concurs that open and arthroscopic joint debridement can improve function in patients with moderate-to-severe OA of the elbow. TEA is reserved for treating severe joint destruction, mostly for elderly individuals with low physical demands when other intervention options have failed.